STRATEGIES TO INCREASE THE NON-TAX REVENUE OF IMMIGRATION SUBJECT TO THE PRESIDENTIAL DECREE NO.21 OF 2016 ON VISA WAIVER PROGRAM - Intan Nurkumalawati (Jurnal Ilmiah Kajian Keimigrasian, 2018)
This paper discusses the phenomena of Visa Waiver Program policy under the Presidential Regulation No. 21 of 2016 on Free Visa Policy in which there are 169 countries being exempted from obtaining a visa to enter the Indonesian territory. Since then, this policy affects a significant decrease of the non-tax revenue of Immigration which might cause the programs and immigration policy getting fewer. The purpose is to set up recommended strategies to raise the number of non-tax revenue of immigration and as a reference and recommendation for Directorate General of Immigration (DGI). The result shows that there are three steps and strategies in an effort to make the non-tax revenue of immigration higher: increasing the fee of the existing non-tax revenue, regulating the discrimination of fee (user charges) of the non-tax revenue, and adding categories of non-tax revenue of immigration.